The Influence of Working Capital Turnover and Company Size on Company Value with Profitability As a Mediating Variable - Sugianto, Pedro Avelino (Pelopor Publikasi Akademika, 2023)
This study aims to determine the effect of working capital turnover and company size on company value which is mediated by profitability in the hotel, resort and cruise ship subsector companies on the Indonesia Stock Exchange for the period 2015 - 2019. This research technique was carried out by purposive sampling with a sample of 14 companies in the hotel, resort and cruise ship subsector that published financial reports and were listed on the Indonesia Stock Exchange for the 2015-2029 period. Testing in this research was carried out with the SEM-PLS software program. The results of this study prove that capital turnover has a negative and significant effect on profitability, company size has a positive and significant effect on profitability, capital turnover has no significant effect on firm value, company size has a positive and significant effect on firm value, profitability has a positive and significant effect on firm value.